2019
DOI: 10.1123/jcsp.2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Equestrian Sport

Abstract: Equestrian media is showing an increasing interest in the impact of mental health on performance and general wellbeing of equestrian athletes. This study explores the awareness of mental health difficulties and psychological wellbeing within equestrian sport from the perspectives of equestrian athletes, instructors/coaches and parents. The exploratory nature of the research offered opportunity to use a dual approach including e-surveys and semi-structured interviews. Analysis of the qualitative data identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In equestrian sport, athletes uniquely depend on a partnership with a horse for success (Meyers et al , 1999). Equestrian sport culture, like many others, has only recently begun to appreciate the mental health challenges associated with the sport (Butler-Coyne et al , 2019). This research seeks to develop current awareness of mental health in equestrian athletes and inform efforts to promote positive mental health for this athlete population.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In equestrian sport, athletes uniquely depend on a partnership with a horse for success (Meyers et al , 1999). Equestrian sport culture, like many others, has only recently begun to appreciate the mental health challenges associated with the sport (Butler-Coyne et al , 2019). This research seeks to develop current awareness of mental health in equestrian athletes and inform efforts to promote positive mental health for this athlete population.…”
Section: Introductionmentioning
confidence: 99%
“…One should consider the potential negative impact of sport on well-being alongside the positive. Butler-Coyne et al (2019) found that participation in equestrian sport negatively impacted equestrian athletes’ well-being in several ways. Maintaining a “sport-life” balance was particularly challenging due to high time demands for training and associated financial pressures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations